MONTHLY RATES OF CELL CYCLE OF RAT ADRENAL GLANDS AFTER BURN AND IN ADMINISTRATION OF 0.9% NACL SOLUTION, LACTOPROTEIN WITH SORBITOL AND HAES-LX-5% - Dzevulska, І.V. (World of Medicine and Biology, 2015)
The paper presents the results of the analysis of monthly rates of cell cycle of rat adrenal glands and DNA-fragmentation after the II-III degree burn with superficial burn surface of 21-23 % in administration of 0.9 % NaCl solution, lactoprotein with sorbitol and HAES-LX-5%. Burn injuries along with infusion of 0.9 % NaCl solution during the first 7 days of the experiment is accompanied by a significant increase of rates of SUB-G0G1 interval and S-phase of adrenal cells after 1, 3, 7 and 14 days after burn. Following the 21 and 30 days after burn no significant difference in the rate of S-phase in the adrenal cells against the similar rate in groups without burn is found, whereas the rate of SUB-G0G1 interval remains reliably higher than those in groups without burn. Thermal burn-related administration of lactoprotein with sorbitol and HAES-LX-5% solutions during the first 7 days of the experiment is accompanied by the positive effect on the rates of SUB-G0G1 interval and S-phase of adrenal cells following the 1, 3, 7 and 14 days after burn. And following the 21 and 30 days after burn the value of the abovementioned rates was almost the same as compared with similar rates in groups where infusion therapy was carried out to animals without burn.